Aerobic methanotrophy increases the net iron reduction in methanogenic lake sediments - Vigderovich, Hanni; Eckert, Werner; Elvert, Marcus; Gafni, Almog; Rubin-Blum, Maxim; Bergman, Oded; Sivan, Orit (Frontiers in Microbiology, 2023)
In methane (CH4) generating sediments, methane oxidation coupled with iron reduction was suggested to be catalyzed by archaea and bacterial methanotrophs of the order Methylococcales. However, the co-existence of these aerobic and anaerobic microbes, the link between the processes, and the oxygen requirement for the bacterial methanotrophs have remained unclear. Here, we show how stimulation of aerobic methane oxidation at an energetically low experimental environment influences net iron reduction, accompanied by distinct microbial community changes and lipid biomarker patterns. We performed incubation experiments (between 30 and 120 days long) with methane generating lake sediments amended with 13C-labeled methane, following the additions of hematite and different oxygen levels in nitrogen headspace, and monitored methane turnover by 13C-DIC measurements. Increasing oxygen exposure (up to 1%) promoted aerobic methanotrophy, considerable net iron reduction, and the increase of microbes, such as Methylomonas, Geobacter, and Desulfuromonas, with the latter two being likely candidates for iron recycling. Amendments of 13C-labeled methanol as a potential substrate for the methanotrophs under hypoxia instead of methane indicate that this substrate primarily fuels methylotrophic methanogenesis, identified by high methane concentrations, strongly positive δ13CDIC values, and archaeal lipid stable isotope data. In contrast, the inhibition of methanogenesis by 2-bromoethanesulfonate (BES) led to increased methanol turnover, as suggested by similar 13C enrichment in DIC and high amounts of newly produced bacterial fatty acids, probably derived from heterotrophic bacteria. Our experiments show a complex link between aerobic methanotrophy and iron reduction, which indicates iron recycling as a survival mechanism for microbes under hypoxia.